Strain-dependent and distinctive T-cell responses to HIV antigens following immunisation of mice with differing chimpanzee adenovirus vaccine vectors. Issue 37 (17th August 2016) - Herath, S.; Le Heron, A.; Colloca, S.; Patterson, S.; Tatoud, R.; Weber, J.; Dickson, G.
Abstract: In vivo vaccination studies are conventionally conducted in a single mouse strain with results, only reflecting responses to a single immunogenetic background. We decided to examine the immune response to an HIV transgene ( gag, pol and nef fusion protein) in 3 strains of mice (CBA, C57BL/6 and BALB/c) to determine the spectrum of responses and in addition to determine whether the serotype of the adenoviral vector used (ChAd3 and ChAd63) impacted the outcome of response. Our results demonstrated that all three strains of mice responded to the transgene and that the magnitude of responses were different between the strains. The C57BL/6 strain showed the lowest range of responses compared to the other strains and, very few responses were seen to the same peptide pool in all three strains of mice. In CBA and BALB/c mice there were significant differences in IFNγ production dependent on the adenoviral vector used. Our results suggest that employing a single strain of mouse may underestimate the efficacy and efficiency of vaccine products.